2017
DOI: 10.1037/apl0000155
|View full text |Cite
|
Sign up to set email alerts
|

Increasing pro-environmental behaviors by increasing self-concordance: Testing an intervention.

Abstract: Concordance: Testing an InterventionGlobally, there is a clear need to change our behavior to mitigate climate change. Many people, however, will not find the need for mitigation important enough to make their behavior more environmentally sustainable. Three studies supported the hypothesis that it is possible to overcome this issue by connecting these behaviors to goals that are important to people, even if such goals are unrelated to climate change or the environment in general.Study 1 (N = 305 working adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 98 publications
0
28
0
Order By: Relevance
“…In general, past studies confirmed the role of values in motivating action on behalf of the cause (Liss, Crawford, & Popp, ; Miller & Krosnick, ; Unsworth & McNeill, ; Van Zomeren, Postmes, Spears, & Bettache, ). For instance, Unsworth and McNeill () showed that the degree to which environmentally sustainable behaviors serve the person's own pre‐existing values predict intentions to engage in sustainable energy behavior.…”
Section: Activism As a Reaction To Negative Experiencesmentioning
confidence: 67%
See 1 more Smart Citation
“…In general, past studies confirmed the role of values in motivating action on behalf of the cause (Liss, Crawford, & Popp, ; Miller & Krosnick, ; Unsworth & McNeill, ; Van Zomeren, Postmes, Spears, & Bettache, ). For instance, Unsworth and McNeill () showed that the degree to which environmentally sustainable behaviors serve the person's own pre‐existing values predict intentions to engage in sustainable energy behavior.…”
Section: Activism As a Reaction To Negative Experiencesmentioning
confidence: 67%
“…In general, past studies confirmed the role of values in motivating action on behalf of the cause (Liss, Crawford, & Popp, ; Miller & Krosnick, ; Unsworth & McNeill, ; Van Zomeren, Postmes, Spears, & Bettache, ). For instance, Unsworth and McNeill () showed that the degree to which environmentally sustainable behaviors serve the person's own pre‐existing values predict intentions to engage in sustainable energy behavior. Also, studies on moral convictions (Skitka & Bauman, ; Skitka, Bauman, & Sargis, ) and sacred values (Atran, Axelrod, & Davis, ; Atran & Ginges, ) showed that they were positively related to political engagement.…”
Section: Activism As a Reaction To Negative Experiencesmentioning
confidence: 67%
“…4) The Self-Concordance Model [15] is based on the idea that it is possible to improve the (sustainable) behaviour connecting specific behaviours with goals which are important to the individual. Although this model has been applied in another context, to the best of our knowledge there is only one related to energy efficiency: a recent study developed by Unsworth and McNeil [16] where an intervention is tested, validating the idea that connecting the goals and pro-environmental behaviour, the latter can be improved.…”
Section: A Theoretical Models For Behaviour Changementioning
confidence: 99%
“…Some studies examined the impact of specific motivation (e.g. competitive and ecological motivations, and self-concordance) on environmental proactivity or pro-environmental behaviors (Walker et al, 2014;Unsworth and McNeill, 2017), but they did not structure hypothetical models within a robust theoretical boundary in the field of individual psychology. Recent studies revealed the complex relation between GO and firm performance (Gimenez et al, 2012;Esfahbodi et al, 2016;Wijethilake, 2017).…”
Section: Introductionmentioning
confidence: 99%